Defending the status quo across venues and coalitions: evidence from California interest groups. (17th August 2016) - Varone, Frédéric; Ingold, Karin; Jourdain, Charlotte
Abstract: This study investigates the conditions under which pro-status quo groups increase their advocacy success during an entire policymaking process. It scrutinises whether pro-status quo defenders who are involved in multiple institutional venues and who join many coalitions of interest groups are able to achieve their policy preferences. A case study focussing on the regulation of stem cell research in California traces the policymaking process and the related advocacy activities of interest groups in legislative, administrative, judicial and direct democratic venues. The empirical results, which are based on a formal social network analysis, reveal that very few groups are multivenue players and members of several coalitions. In addition, occupying a central network position is insufficient for the pro-status quo groups to improve their advocacy success.